Pathogen identification and genotyping of two cluster outbreaks of herpangina in children in Dapeng New District， Shenzhen - HUANG Miaofen; WANG Wenxiang; LIAN Xianqiang; YANG Yue (Shanghai yufang yixue, 2022)
ObjectiveTo determine the pathogenic characteristics and genotype of two outbreaks of herpangina in children in Dapeng New District， Shenzhen， in May 2021.MethodsA total of five throat swabs from children in the two outbreaks of herpangina were collected and examined for common enteroviruses by real-time PCR. The VP1 region was further amplified by nested RT-PCR. The CLUSTAL W program in MEGA7 software was used to conduct the alignment and reconstruct a phylogenetic tree.ResultsThe pathogen causing the 2 cluster outbreaks of herpangina was coxsackievirus A4 （CVA4）. The sequences of CVA4 VP1 genes revealed that a nucleotide identity of 92% between the strains in the two outbreaks. The three CVA4 strains isolated in kindergarten A had the closest phylogenetic relationship with that isolated in Shenzhen in 2018（MN840533）， with the nucleotide identity of 98.11%. The two strains in kindergarten B had the closest phylogenetic relationship with CVA4 strain isolated in Sichuan in 2018（MW178763）， with the nucleotide identity of 97.88%. The phylogenetic tree showed that all five CVA4 strains in this study belonged to the C2 genotype.ConclusionThe C2 genotype of CVA4 is the causative agent in both outbreaks of herpangina.